Do stability and size affect the profitability of Islamic rural bank in Indonesia? - Heri Sudarsono; Fiqih Afriadi; Siti Aisiyah Suciningtias (Faculty of Economics, Universitas Islam Indonesia, 2021)
Purpose – This study aims to analyze the effect of stability, size, financial performance and macroeconomic variables on the profitability of Islamic Rural Banks (BPRS) in Indonesia.Methodology – This study uses panel data consisting of 82 BPRS from December 2012 to December 2018. This study uses a dynamic model using GMM (General Method of Moments) developed by Arellano & Bover (1995) and Blundell & Bond (1998). GMM is used to describe the actual conditions in the analysis of profitability of Islamic Rural Banks.Findings – The findings of this study indicate that the stability and size of the BPRS have a negative effect on the level of ROA and ROE. Further, BAC has a positive effect on ROA but it has a negative effect on ROE. While the deposit structure (DS) is found to have a positive effect on ROA and ROE, FDRand the total deposit (DAR) is found to have a positive effect on both ROA and ROE. Meanwhile, the capital structure does not show a significant value on ROA. On the other hand, economic growth (GDP) and inflation (INF) do not show a significant relationship to ROA, but inflation is positively related to ROE.Originality – This study is to determine the effect of the stability and the size of BPRS on its profitability. This study uses 6 models to obtain a consistent variation of variables in influencing profitability.